POSTHUMANISM AND TECHNOLOGICAL DEPENDENCE IN RAY BRADBURY'S THE VELDT - Jonorman, Khairunisha Amshalia; Salsabila, Alma; Caroline, Gita Melynia; Christianto, Daniel Ganda; Irwan, Avita Yuliana; Wardani, L.Dyah Purwita (ELITERATE : Journal of English Linguistics and Literature Studies, 2024)
This study provides the complex relationship between humans and technology, specifically focusing on the impact of over-reliance on advanced technological systems as depicted in Ray Bradbury's short story The Veldt. It discusses the evolution of human and technological interaction, highlighting its potential risks. Using a qualitative methodology, this research analyzes the narrative elements of The Veldt to illustrate the impact of technological dependence on human relationships. The research explores posthumanism, questioning the centrality of humans in an era of technological advancement and the blurring of boundaries between reality and virtual environments. There are three aspects found in the findings of this research that examine the interaction between humans and technology, which are: the posthuman aspect, the consequences of reality and the virtual environment, and technological dependence in general. The Veldt narrative serves as a cautionary tale about the dangers of over-reliance on technology, emphasizing the need for a balanced application of technology into human life to maintain genuine human relationships and roles.